2021
DOI: 10.3390/plants10061069
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Citrus Co-Products: Recovery of Bioactive Compounds and Application in Meat and Meat Products

Abstract: Citrus fruits (orange, lemon, mandarin, and grapefruit) are one of the most extensively cultivated crops. Actually, fresh consumption far exceeds the demand and, subsequently, a great volume of the production is destined for the citrus-processing industries, which produce a huge quantity of co-products. These co-products, without proper treatment and disposal, might cause severe environmental problems. The co-products obtained from the citrus industry may be considered a very important source of high-added-val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 132 publications
0
28
0
Order By: Relevance
“…Although there is controversial evidence regarding the bioavailability of carotenoids in human and animal models [ 41 ], the improvement of meat oxidative stability through carotenoids dietary inclusion portrays a well-documented scenario [ 6 ]. In agreement with our study, the dietary supplementation with commercial rich in astaxanthin product decreased the TBARS content in broilers muscles kept in both thermoneutral and high ambient temperature conditions [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is controversial evidence regarding the bioavailability of carotenoids in human and animal models [ 41 ], the improvement of meat oxidative stability through carotenoids dietary inclusion portrays a well-documented scenario [ 6 ]. In agreement with our study, the dietary supplementation with commercial rich in astaxanthin product decreased the TBARS content in broilers muscles kept in both thermoneutral and high ambient temperature conditions [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…A significant volume of this production is originated in the food industry and majorly for juice, jams, beverages, etc. [ 6 ]. Amongst these fruits, 50–60% are discarded, and consequently plenty of difficult to stock sought-after bioactive compounds are wasted as well [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…peel and pulp are a rich source of various active ingredients, such as dietary fiber, minerals, vitamins, organic acids, flavonoids (ferulic, sinapic acids, and chlorogenic), phenolics (hesperetin, hesperidium, diosmin, and narirutin), carotenoids (carotene, zeaxanthin, lutein) [192][193][194][195]. These compounds are applied in the meat industry due to their associated health effects, such as antimicrobial, antioxidant, anticancer, anti-allergic, and antihypertensive effects [196]. The antioxidant activity of different citrus extracts varies with the methodology of their extraction, their fruit type, their environmental conditions, such as soil type and climate, their fruit-ripening stage, and their harvesting time [197,198].…”
Section: Plant Extracts As Natural Antioxidants In Meatmentioning
confidence: 99%
“…The wastes deriving from Citrus processing (peels and seeds in primis) are an important part, and various papers have shown that by recycling and using these parts, bioactive compounds such as flavonoids, limonoids, terpenoids, and minerals can be obtained [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%